Acute kidney injury and cardiogenic shock severity for mortality risk stratification in patients supported with VA ECMO - Chenglong Li; Yiwen Wang; Xiaomeng Wang; Chengcheng Shao; Meng Xin; Bo Xu; Xing Hao; Ming Jia; Feng Yang; Liangshan Wang; Hong Wang; Xiaotong Hou; et al. (ESC Heart Failure, 2024)
Abstract Aims To assess the stage of acute kidney injury (AKI), as an index of organ perfusion, combined with shock severity, measured by the Society for Cardiovascular Angiography and Interventions (SCAI) shock stage classification, to stratify the risk of mortality in patients diagnosed with cardiogenic shock (CS) and supported with venoarterial extracorporeal membrane oxygenation (VA ECMO). Methods ans results From January 2018 to December 2020, consecutive adult patients diagnosed with CS and received VA ECMO were retrospectively evaluated. The highest AKI stage within 48 h after ECMO initiation was assessed using the Kidney Disease: Improving Global Outcomes criteria. We included 216 patients with a mean age of 58.8 years and 31.0% were females. 88.4% of patients received ECMO for postcardiotomy, while 11.6% for medical CS. The total in‐hospital mortality was 53.2%. AKI occurred in 182 (84.3%) patients receiving ECMO for CS. AKI stage 0, 1, 2, and 3 were present in 15.7%, 17.6%, 18.1%, and 48.6% of patients with in‐hospital mortality of 26.5%, 26.3%, 61.5%, and 68.6%, respectively (P < 0.001). The AKI stage (P < 0.001), SCAI shock stage before ECMO (P = 0.008), and NYHA ≥ Class III on admission (P = 0.044) were independent predictors of in‐hospital mortality. The area under the receiver operating characteristic curve of 0.754 (95% confidence interval: 0.690 to 0.811) for AKI stage combined with SCAI shock stage was better than those for AKI stage (0.676), SCAI shock stage (0.657), serum lactate level (0.682), SOFA score (0.644), SVAE score (0.582), and VIS score (0.530) prior to ECMO. Conclusions In this single‐center CS population who received VA ECMO for circulatory support, predominantly postcardiotomy cases, AKI occurred in 84.3% of the patients. AKI stage, as an index of organ perfusion combined with shock severity measured by the SCAI shock classification, demonstrates a good correlation with in‐hospital mortality.